Linearized Kinetic Theory of Plasma Waves - Alhasi , Awad. S.; Mousa , Asmaa. A.; Elmabrok , abdelhamid. S. (Scientific Journal of University of Benghazi, 2022)
A striking illustration of the shortcomings of the simple fluid description appeared in the dispersion relation obtained in the presence of thermal effects. In this work, it is shown that the substitution of the fluid description with the tools of the kinetic theory leads to solving these limitations. The distribution function f_α is linearized and the Vlasov–Poisson kinetic system is described. The three terms that control the evolution of the perturbed distribution function and their physical effects are discussed.